Serbia: Strict Laws, Liberal Practice - Živković, Miloš (Acquisition of Agricultural Lands, 2022)
The issue of cross-border acquisition of agricultural land is regulated in an inconsistent manner in Serbian law: on the one hand, constitutional provisions are very liberal and impose minimal restrictions to the ownership acquisition of such land by foreign nationals; on the other hand, statutory provisions are extremely restrictive and seem to exclude not only acquisition of ownership of agricultural land by foreign nationals but also the very capacity of non-Serbian nationals to own agricultural land. Given that the Stabilization and Association Agreement between Serbia and EU and its member states, which came into force in 2013, foresaw a 4-year deadline for Serbia to equalize the legal position of EU member states nationals with Serbian nationals in respect of the conditions for the acquisition of ownership of agricultural land, the statutory provisions were altered in 2017. However, these amendments not only failed in the abovementioned objective, but they contained such complex conditions for EU member state nationals to acquire agricultural land in Serbia that it made it impossible at least until 2027 and practically impossible even after that year. This is confirmed when the existing conditions are analyzed from the point of view of the 2017 Commission Interpretative Communication on the Acquisition of Farmland and EU law. This Communication analyzed the restrictions imposed by EU countries to the acquisition of agricultural land by both domestic and EU member state nationals from the point of view of EU law. Many of the conditions that exist in Serbia only for EU member states nationals would not adhere to EU law even if they applied to Serbian and EU member states nationals equally. This is reflected in the recent annual reports of the European Commission on the state of relations between Serbia and the EU, where it is noted that the obligation to equalize the position of domestic and EU member state nationals in respect of the acquisition of agricultural land contained in the SAA is not fulfilled. All this is in sharp contrast with the fact that, in practice, foreign nationals may acquire the ownership of agricultural land in Serbia indirectly, by establishing a legal entity in Serbia, or even directly, if such right is provided in an international treaty. Such inconsistent regulation and commercial practice are highly likely to cause further friction and political debate in Serbia in the coming years.Keywords: ownership acquisition, agricultural land, right of foreigners